Sifat Kimia Dan Organoleptik Cookies Bebas Gluten Bebas Kasein Berbasis Tepung Komposit Mocaf Dan Kacang Merah - Ayuningtyas, Tri Nuria; Sofyan, Aan (Dinasti Research, 2025)
Autism is a developmental disorder that can affect cognitive behavior and social behavior, with varying symptoms in each individual. Nutritional therapy can reduce autistic symptoms. Cookies made from composite flour of mocaf and red beans can be alternative as gluten and casein free snacks suitable for individuals with autism. Cookies are snacks made from a variety of ingredients and can be used as an option to meet nutritional requirements. This study aims to analyze the chemical dan organoleptic properties of cookies based on composite flour of mocaf and red beans. The experimental study used a completely randomized design (CRD), with varying proportions of mocaf flour and red beans flour: F1(55:45), F2 (70:30), F3 (85:15) and F0 (100%) wheat flour as a control. The result show that using composite flour significantly affect fiber, fat, and protein content (p-value < 0,05). The highest fiber content was found in F2 was 6.02%, the highest fat content in F3 was 18.10%, and the highest protein content in F0 was 7.40%. The organoleptic test result that there are significant effects on sensory attributes such as taste, texture and overall acceptability. Cookies F3 (85:15) are the most preferred by panelists, with fiber, fat and protein already pass Indonesian National Standard.